2018
DOI: 10.1002/jcp.26629
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pannexin 1 and Pannexin 3 during skeletal muscle development, regeneration, and Duchenne muscular dystrophy

Abstract: Pannexin 1 (Panx1) and Pannexin 3 (Panx3) are single membrane channels recently implicated in myogenic commitment, as well as myoblast proliferation and differentiation in vitro. However, their expression patterns during skeletal muscle development and regeneration had yet to be investigated. Here, we show that Panx1 levels increase during skeletal muscle development becoming highly expressed together with Panx3 in adult skeletal muscle. In adult mice, Panx1 and Panx3 were differentially expressed in fast- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 58 publications
(117 reference statements)
4
25
1
Order By: Relevance
“…Pannexins (PANX1, PANX2, and PANX3) are single membrane channels that allow the release of small molecules such as nucleotides [8]. Our work has shown that PANX1 levels are low in undifferentiated skeletal muscle myoblasts and increase during myogenesis in vitro and in vivo [6,9]. Blocking PANX1 channel activity inhibited myoblast differentiation, while PANX1 overexpression promoted this process [6].…”
Section: Introductionmentioning
confidence: 87%
“…Pannexins (PANX1, PANX2, and PANX3) are single membrane channels that allow the release of small molecules such as nucleotides [8]. Our work has shown that PANX1 levels are low in undifferentiated skeletal muscle myoblasts and increase during myogenesis in vitro and in vivo [6,9]. Blocking PANX1 channel activity inhibited myoblast differentiation, while PANX1 overexpression promoted this process [6].…”
Section: Introductionmentioning
confidence: 87%
“…Pannexin hemichannels were reported to mediate ATP release upon electrical stimulation [ 92 , 93 ], mechanical stress, and elevated extracellular potassium ion concentration [ 94 ]. Pannexin (PANX) 1 and 3 are expressed by myoblasts and SCs and are involved in the regulation of myoblast proliferation, differentiation and skeletal muscle development [ 92 , 95 , 96 ]. PANX1 levels are dramatically induced during myoblast differentiation, whereas PANX3 is mainly expressed in differentiated human skeletal muscle tissue, and its over-expression inhibits myoblast proliferation and induces their differentiation [ 95 , 96 ].…”
Section: Other Regulators Of P2x7r Signalingmentioning
confidence: 99%
“…In addition, PANX1 regulates the oxidative state during exercise [ 100 ]. PANX3 has also been demonstrated to mediate eATP release [ 101 ], likely being involved in contraction and metabolism [ 96 ].…”
Section: Other Regulators Of P2x7r Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy cells PANX1 channels normally remain in a closed state until induced to transiently open in response to a variety of stimuli including membrane deformation, receptor activation, and intracellular calcium release (Sandilos et al, 2012;Bao et al, 2013;Furlow et al, 2015;Sanchez-Arias et al, 2019). PANX1 signaling can also influence the self-renewal and differentiation of multiple somatic (adult) stem cell types including osteoprogenitor cells, skeletal myoblasts, and postnatal neural precursor cells (Wicki-Stordeur et al, 2012;Wicki-Stordeur and Swayne, 2013;Wicki-Stordeur et al, 2016;Ishikawa and Yamada, 2017;Pham et al, 2018). However, much less is known about the impact of PANX1 signaling in the early embryo or in pluripotent stem cells (Hainz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%